Pengaruh Brand Image Dan Social Media Marketing Terhadap Purchase Decision Melalui Brand Trust Sebagai Variabel Intervening Pada Produk Kecantikan Hanasui (Studi Kasus Pada Gen Z Kota Malang) - Afiani, Maulina Nur; Wahono, Budi; Bastomi, Mohamad (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This research aims to explore and analyze the influence of Brand Image and Social Media Marketing on Purchase Decisions through Brand Trust as an intervening variable in the case of Hanasui beauty products among Generation Z in Malang City. The study employed a quantitative approach, with data collected through questionnaires distributed to respondents. The research involved 85 Generation Z respondents who are users of Hanasui beauty products in Malang City. The sampling technique used was purposive sampling. The collected data was processed using the SmartPLS analysis tool with the Structural Equation Modeling (SEM)-PLS method. The results of the study indicate that Brand Image and Social Media Marketing do not have a significant effect on Purchase Decisions. However, Brand Image and Social Media Marketing have a significant influence on Brand Trust. Brand Trust also significantly affects Purchase Decisions. Furthermore, Brand Trust positively and significantly mediates the relationship between Brand Image and Social Media Marketing on Purchase Decisions. Keywords: Brand Image, Social Media Marketing, Brand Trust, Purchase Decision.